2024
DOI: 10.3390/nu16060773
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Habitual Polyphenol Consumption and Gut Microbiota in the INCLD Health Cohort

Alexandra Adorno Vita,
Kristen M. Roberts,
Anders Gundersen
et al.

Abstract: While polyphenol consumption is often associated with an increased abundance of beneficial microbes and decreased opportunistic pathogens, these relationships are not completely described for polyphenols consumed via habitual diet, including culinary herb and spice consumption. This analysis of the International Cohort on Lifestyle Determinants of Health (INCLD Health) cohort uses a dietary questionnaire and 16s microbiome data to examine relationships between habitual polyphenol consumption and gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…In addition, many of the studies reported only on one or two health outcomes and so data was lacking particularly for self-rated health, cholesterol, muscle mass and hand grip strength. However, we know that previous work has demonstrated that both animal and plant proteins can be incorporated into a healthy diet to reduce risk of age-related diseases [76,77] and habitual consumption of polyphenols from fruit, vegetables, nuts, herbs and spices may support an intestinal environment with lower relative abundance of pathogenic bacteria [78].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many of the studies reported only on one or two health outcomes and so data was lacking particularly for self-rated health, cholesterol, muscle mass and hand grip strength. However, we know that previous work has demonstrated that both animal and plant proteins can be incorporated into a healthy diet to reduce risk of age-related diseases [76,77] and habitual consumption of polyphenols from fruit, vegetables, nuts, herbs and spices may support an intestinal environment with lower relative abundance of pathogenic bacteria [78].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al, 2019 [53] showed changes in 26 microbial operational taxonomic units in participants taking 5 g mixed-spice capsules daily for 2 weeks. Further, in an observational study, Vita et al (2022Vita et al ( , 2024) observed significant beneficial changes in the GM profile in association with higher intakes of herbs/spices and polyphenols [51,53,56,57]. The fermentation of prebiotics by gut microbiota results in the production of SCFAs, including lactic acid, butyric acid, and propionic acid.…”
Section: Prebiotic Potential Of Herbs and Spicesmentioning
confidence: 99%
“…Polyphenols also have promoting effects on Akkermansia muciniphila, an anaerobic and mucosa-associated colonic bacterium with mucin-degrading capabilities [137]. Recent findings conclude that microbial taxa but not diversity are promoted by habitual polyphenol consumption [138]. This implies that future research should focus on specific microbial biomarkers and their changes due to polyphenol exposure.…”
Section: Wellbeing and Prevention Through Nutritionmentioning
confidence: 99%